(untitled) (Semiárida, 2018)
Frosts can cause a great damage to agricultural production, depending on their intensityand time of occurrence, as well as crop development stage. The frost regime of Anguil, La Pampa province, was characterized using minimum temperatures recorded daily above ground at 1.50 m in weather box and 0.05 m during the period 1973-2009. Frosts were classified into ranges (mild, moderate, strong and very strong) depending on their intensity. Calculations of first and last frost mean dates and their variability, along with average lengthof the frost and frost-free periods for the entire series and for each defined intensity range,were performed. Frosts occurring at 0.05 m above ground are of agricultural importance,considering that the average frost-free period is shorter at that height in comparison to thecorresponding one for 1.50 m, where as the number of days for the frost period near thesoil surface is higher. The occurrence of very strong frosts was five times higher, and with greater deviations, at 0.05 m than at 1.50 m. Recorded first and last frost mean dates, at both height levels considered, show a high hazardousness for the flowering and fructification stages for both small grain and coarse grain crops, and for the emergency of the last ones.